Telemetry-assisted early detection of STEMI in patients with atypical symptoms by paramedic-performed 12-lead ECG with subsequent cardiological analysis. (August 2017) - Campo Dell' Orto, Marco; Hamm, Christian; Liebetrau, Christoph; Hempel, Dorothea; Merbs, Reinhold; Cuca, Colleen; Breitkreutz, Raoul
Abstract : Objectives: ECG is an essential diagnostic tool in patients with acute coronary syndrome. We aimed to determine how many patients presenting with atypical symptoms for an acute myocardial infarction show ST-segment elevations on prehospital ECG. We also aimed to study the feasibility of telemetric-assisted prehospital ECG analysis. Patients and methods: Between April 2010 and February 2011, consecutive emergency patients presenting with atypical symptoms such as nausea, vomiting, atypical chest pain, palpitations, hypertension, syncope, or dizziness were included in the study. After basic measures were completed, a 12-lead ECG was written and telemetrically transmitted to the cardiac center, where it was analyzed by attending physicians. Any identification of an ST-elevation myocardial infarction resulted in patient admission at the closest coronary angiography facility. Results: A total of 313 emergency patients presented with the following symptoms: dyspnea, nausea, vomiting, dizziness/collapse, or acute hypertension. Thirty-four (11%) patients of this cohort were found to show ST-segment elevations on the 12-lead ECG. These patients were directly admitted to the closest coronary catheterization facility rather than the closest hospital. The time required for transmission and analysis of the ECG was 3.6±1.2 min. Conclusion: Telemetry-assisted 12-lead ECG analysis in a prehospital setting may lead to earlier detection of ST-elevation myocardial infarction in patients with atypical symptoms. Thus, a 12-lead ECG should be considered in all prehospital patients both with typical and atypical symptoms.